Desa Wisata Indonesia (Transformasi Ekonomi Berbasis Asset-Based Community Development Menuju Swasembada) - Kamal Ramadhani; Mia Liliawati; Rista Maulidina; Ita Nuryana; Dyah Maya Nihayah (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
This study aims to examine the factors of success and challenges in implementing asset-based community development in tourist villages, to achieve self-sufficient villages in Indonesia. The approach used in this study is a systematic literature review conducted through a process of selecting and analyzing previous literature from books and articles. The book referenced in this study is Hill's book, supported by 18 articles that have been synthesized. Data analysis was conducted using content analysis techniques to identify key factors that support and hinder the success of asset-based community development (ABCD) in the context of tourist villages in Indonesia. The study's results indicate that the asset-based community development strategy is crucial for building a resilient, sustainable, and inclusive local economy. The ABCD approach has been proven to strengthen collaboration among stakeholders. Successful ABCD initiatives in village self-sufficiency can have a significant impact on poverty reduction and improve welfare. Some key factors for the success of ABCD include: strong leadership and institutions, community capacity and empowerment, policy support and funding, and multi-stakeholder collaboration. Challenges in implementing ABCD to achieve self-sufficient villages include: community dependence on government assistance, limited infrastructure and technology, conflicts of interest and social fragmentation, as well as threats from climate change and resource exploitation. The successful ABCD concept can be disseminated for implementation in various villages in Indonesia, thereby creating self-sufficient villages. The success of ABCD is driven by active community participation, with a vision that aligns with utilizing the surrounding nature and culture. The implementation of ABCD creates a multiplier effect on various actors. Optimal implementation of ABCD can lead to self-sufficient villages. However, the challenge of community dependence on the government remains a significant obstacle. Therefore, further research is needed to examine efforts to address the challenges outlined in this study for ABCD through practical implementation in communities.